A new genus and three new species of Monorchiidae (Trematoda) from freshwater fish of Rondônia State, Brazil - Thatcher, Vernon E. (Amazoniana, 1996)
A new genus and three new species of freshwater Monorchiidae (Trematoda) are described from the intestinal tracts of fish of Rondonia State, Brazil. Sphericomonorchis spinulosus gen. et sp. nov. from Crenicichla Johanna HECKEL, is characterized as having a small, compact body, a large, spherical testis near the posterior extremity and vitelline follicles lateral to the acetabulum. Paraproctotrema delicata sp. nov., from Boulengerella lucia (CUVIER), is a slender species having a large acetabulum with vitellaria postero-lateral to it, a small cirrus sac and post-testicular uterine loops. The third species, Genolopa magnacirrus sp. nov., from the same host, has a cirrus sac from thirty to fifty percent of the body length, a testis near the posterior extremity and vitellaria well posterior to the acetabulum.